Queer-trans-straight alliances: disrupting cisheteronormativity on university campuses in the Western Cape Province, SA - Bimha, P.Z.J.; Francis, D. (South African Journal of Higher Education, 2025)
The Western Cape province is home to four universities ‒ all of which host queer-trans-straight alliances committed to promoting education and advocacy to tackle the marginalisation of lesbian, gay, bisexual, transgender, intersex, queer/questioning, and asexual (LGBTIQ+) students. These alliances include Stellenbosch University’s QueerUS Society, the University of Cape Town’s (UCT) Rainbow Society, the University of Western Cape’s (UWC) LoudEnuf Society, and Cape Peninsula University of Technology (CPUT) Queer Unicorns. This article offers a comprehensive analysis of the research literature, reports, and media documenting the efforts of these four queer-trans-straight alliances in the Western Cape to highlight their pivotal role in promoting institutional policy reforms and raising social awareness and change initiatives. Using Livermon’s concept of queer labour, this article spotlights the efforts undertaken by queer-trans-straight alliances and argues that they play a pivotal role in destabilising the representation of cisheteronormative cultures and ideologies promoting visibility and inclusion for LGBTIQ+ communities in higher education. The article concludes by exploring how queer labour facilitates queer-trans-straight alliances, social awareness, and change processes in higher education.